New X-ray observations of the hot subdwarf binary HD 49798/RX J0648.0–4418. Issue 1 (10th April 2021) - Mereghetti, S; Pintore, F; Rauch, T; La Palombara, N; Esposito, P; Geier, S; Pelisoli, I; Rigoselli, M; Schaffenroth, V; Tiengo, A
ABSTRACT: HD 49798/RX J0648.0–4418 is the only confirmed X-ray binary in which the mass donor is a hot subdwarf star of O spectral type and, most likely, it contains a massive white dwarf (1.28 ± 0.05 M⊙ ) with a very fast spin period of 13.2 s. Here, we report the results of new XMM–Newton pointings of this peculiar binary, carried out in 2018 and in 2020, together with a reanalysis of all the previous observations. The new data indicate that the compact object is still spinning-up at a steady rate of (−2.17 ± 0.01) × 10 −15 s s −1, consistent with its interpretation in terms of a young contracting white dwarf. Comparison of observations obtained at similar orbital phases, far from the ecplise, shows evidence for long-term variability of the hard (>0.5 keV) spectral component at a level of ∼(70 ± 20) per cent, suggesting the presence of time-dependent inhomogeneities in the weak stellar wind of the HD 49798 subdwarf. To investigate better the soft spectral component that dominates the X-ray flux from this system, we computed a theoretical model for the thermal emission expected from an atmosphere with element abundances and surface gravity appropriate for this massive white dwarf. This model gives a best fit with effective temperature of Teff = 2.25 × 10 5 K and an emitting area with a radius of ∼1600 km, larger than that found with blackbody fits. This model also predicts a contribution of the pulsed emission from the white dwarf in the optical band significantly larger than previously thought and possibly relevant for optical variability studies of this system.